1998
DOI: 10.1007/s11746-998-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed synthesis of chiral triglycerides

Abstract: Under certain reaction conditions, the acidolysis of tripalmitin with oleic acid using immobilized lipase from Rhizomucor miehei resulted in a higher level of monosubstituted oleoyldipalmitoyl (OPP) triglycerides than had been predicted according to kinetic modeling. The reaction products were subjected to chiral analysis by high-performance liquid chromatography (HPLC), which indicated that the enzyme was more active at the sn-1 position of the triglyceride than at the sn-3 position, resulting in synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…This assumption has been done to simplify the development and application of the proposed model, however there is experimental evidence that the 1 and 3 positions are significantly different at low conversions for the Rhizomucor miehei lipase. [17][18][19] However, this circumstance has no influence on the obtained results because the 1(3), 2-diglycerides are considered as an unique component.…”
Section: Modelling: Equilibrium and Kinetic Equations 31 Equilibriummentioning
confidence: 99%
“…This assumption has been done to simplify the development and application of the proposed model, however there is experimental evidence that the 1 and 3 positions are significantly different at low conversions for the Rhizomucor miehei lipase. [17][18][19] However, this circumstance has no influence on the obtained results because the 1(3), 2-diglycerides are considered as an unique component.…”
Section: Modelling: Equilibrium and Kinetic Equations 31 Equilibriummentioning
confidence: 99%
“…The high stereospecificity of some lipases makes the synthesis of such triacylglycerols possible [49]. It was found that Rhizomucor miehei lipase shows stereospecificity towards sn-1 position [26] and some other lipases had specificity towards sn-3 position [74]. Therefore, chiral triacylglycerols can be produced if only mono-incorporated products are proceeded.…”
Section: Developed and Marketed Productsmentioning
confidence: 99%
“…Thus, the importance of the water content of the system was shown (Green and Nakajima, 1998;Haraldsson and Thorarensen, 1999;McNeill and Sonnet, 1995;Rosu et al, 1999;Villeneuve et al, 1998). Some studies reported that the water thermodynamic activity (a w ) is conditioning the lipase spatial structure and thus its enzymatic activity either toward synthesis or hydrolysis (Chandler et al, 1998;Soumanou et al, 1998b;Svensson et al, 1994;Valivety et al, 1992Valivety et al, , 1994Villeneuve et al, 1997a;Lee and Foglia, 2000). For synthesis reactions performed with water-free substrates and in a solventfree system, the aqueous phase is limited to the one coming from the enzyme preparation.…”
Section: Introductionmentioning
confidence: 99%